Understanding Defensive Stocks with Company Fundamentals and Dividend Policy Variables as Moderation - Mahfudz, Ali; Wijayanto, Andhi (Universitas Negeri Semarang, 2020)
The purpose of this study was to determine the effect of Return on Equity, Firm Size, Debt Equity Ratio and Price Earning Ratio on return defensive stocks with Dividend Policy as Variable Moderation in Manufacturing Companies. The study population was manufacturing sector companies listed on the Indonesia Stock Exchange from 2015 to 2018. There were 61 companies sampled using purposive sampling techniques. The analytical method uses multiple linear analysis and moderated Regression analysis. The results showed the Firm Size variable had a significant positive effect and the DER variable had no significant positive effect while the ROE and PER variables had no significant negative effect on return defensive stocks. The MRA test states that the Dividend Payout Ratio variable strengthens the effect of Firm Size on return defensive stocks while the ROE, DER and PER variables are weakened by the effect on return defensive stocks by dividend policy. Future studies are expected to use other variables that might increase or decrease stock returns.